Lipase-catalyzed synthesis of sorbitol octanoate in aqueous biphasic medium and its use in a green formulation process of oil-in-water food nanoemulsions - Natcha Wongthongdee (2018)
© 2017 Society of Chemical Industry BACKGROUND: Sugar-based surfactants are highly relevant alternative ingredients for food grade formulations. Nevertheless, the design of sustainable manufacturing processes is still ongoing. RESULTS: Sorbitol ester surfactants were synthesized by lipase-catalyzed esterification in solvent-free conditions. Octanoic acid was dispersed in a 70 wt% sorbitol aqueous solution (containing the enzyme). The maximal conversion of 23.5 mole % of esterified fatty acid per mole of loaded fatty acid was obtained after 48 h in optimal conditions. The performance of the reactor was affected by both the nature and amount of the reactants and the dispersion state. Detailed structural analysis demonstrated that lipase from Candida rugosa specifically catalyzed the acylation of sorbitol on primary hydroxyl groups. Sorbitol esters accumulated exclusively in the oil phase, which led to easy and efficient product recovery. Oil phase containing the sorbitol esters could be used directly for preparing oil-in-water nanoemulsion without adding any other stabilizer. These nanoemulsions exhibited good stability after 7 days storage at 25°C or 60°C. CONCLUSION: A green manufacturing process for food grade oil-in-water nanoemulsions was designed involving a lipase-catalyzed esterification step which produced in situ the required surfactant. Nanoemulsions were prepared without using any other stabilizer. © 2017 Society of Chemical Industry.